Investigating Calquing In Arabic How Translation Can Shape The Future Of Arabic - Albarakati, Mohammed; Alamri, Shuaa (Ijaz Arabi Journal of Arabic Learning, 2025)
This paper investigates the influx of Anglicism and Frenchism into the Arabic lexicon. The focus will be on authentic borrowed English and French phrases that have entered the Arabic lexicon. While social media has introduced a considerable amount of Anglicism and Frenchism into the Arabic language during the 21st century, film translation, TV programs, and translated books have also contributed to this phenomenon, making these calques an integral part of the modern lexicon used by Arab speakers. The study employs a qualitative method to trace these structures across a wide range of texts, as data are retrieved from various online resources and specialized dictionaries to gauge the extent to which Anglicism and Frenchism calquing have impacted modern standard Arabic. Through this approach, the study seeks to uncover the patterns, frequency, and domains of calque integration, thereby offering insight into the linguistic consequences of sustained contact with dominant global languages. Ultimately, the research highlights how Arabic continues to evolve through lexical borrowing and structural adaptation, reflecting broader processes of linguistic convergence in a globalized era.